2016
DOI: 10.1155/2016/6521026
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Reduces the Effects of Acute Noxious Stimulation on the Electrical Activity of Pain-Related Neurons in the Hippocampus of Control and Neuropathic Pain Rats

Abstract: To study the effects of acupuncture analgesia on the hippocampus, we observed the effects of electroacupuncture (EA) and mitogen-activated protein kinase (MEK) inhibitor on pain-excited neurons (PENs) and pain-inhibited neurons (PINs) in the hippocampal area CA1 of sham or chronic constrictive injury (CCI) rats. The animals were randomly divided into a control, a CCI, and a U0126 (MEK1/2 inhibitor) group. In all experiments, we briefly (10-second duration) stimulated the sciatic nerve electrically and recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…14,15 In previous studies, Wang et al suggested that electroacupuncture (EA) reduces the effects of electrical activity of pain-related neurons in the hippocampus of rats with neuropathic pain. 16 Using fMRI, Theysohn et al found that acupuncture could modulate brain activity under pain conditions in the cingulate gyrus, insula, primary somatosensory cortex, and prefrontal areas. 17 However, how EA affects brain metabolism following BPAI-induced pain is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 In previous studies, Wang et al suggested that electroacupuncture (EA) reduces the effects of electrical activity of pain-related neurons in the hippocampus of rats with neuropathic pain. 16 Using fMRI, Theysohn et al found that acupuncture could modulate brain activity under pain conditions in the cingulate gyrus, insula, primary somatosensory cortex, and prefrontal areas. 17 However, how EA affects brain metabolism following BPAI-induced pain is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA) is used to treat neuropathic pain (NP) induced by peripheral nerve injury (PNI) ( 1 , 2 ). To the best of our knowledge, however, the mechanism has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-cell patch clamp techniques were used to investigate the variation in the frequency of spontaneous excitatory postsynaptic currents (sEPSC) in SNL rat spinal substantia gelatinosa (SG) neurons. Studies have demonstrated that EA treatment at ‘Zusanli’ (ST-36, at the posterolateral aspect of the knee joint, ~5 mm below the humeral head) and ‘Kunlun’ (BL-60, ~10 mm above the prominence of the lateral malleolus of the hind limb) points can relieve neuropathic pain, but its specific mechanism has not yet been elucidated ( 1 , 2 ). The aim of the present study was to investigate the potential mechanism by which EA treatment at ‘Zusanli’ and ‘Kunlun’ points relieves NP via the action on P2X4R.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the Sino-Austrian High-Tech Acupuncture Network has grown very fast. In the following, milestones from the year 2017 are listed chronologically and at the end of the report recent literature from the network is cited [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] (see also Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Figure 9 , Figure 10 , Figure 11 , Figure 12 , Figure 13 , Figure 14 , Figure 15 , Figure 16 , Figure 17 , Figure 18 , Figure 19 , Figure 20 , Figure 21 , Figure 22 , Figure 23 , Figure 24 , Figure 25 , Figure 26 , Figure 27 , Figure 28 , Figure 29 , Figure 30 , Figure 31 , Figure 32 , Figure 33 and Figure 34 ):…”
mentioning
confidence: 99%